FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA KEPERAWATAN MENJADI RELAWAN BENCANA COVID-19 : STUDI LITERATUR - Novida Prima Wijayanti; Kurniawan Bagus Sugiarto (Jurnal Keperawatan Karya Bhakti, 2024)
Covid-19 is an infectious disease caused by coronavirus with common symptoms of fever, weakness, cough, anosmia and diarrhea. In 2020, the World Health Organization has designated Covid-19 as a non-natural pandemic disaster. The increasing number of Covid-19 sufferers has caused an increase in the need for health workers from volunteers, especially from nursing students. Student preparedness can be started from the academic level to increase the desire to volunteer during a pandemic disaster. Objective: this study aims to analyze factors that can influence the desire of nursing students to volunteer during the COVID-19 disaster. Method: The type of research used is a type of quantitative research descriptively cross sectional and takes research sources that have been carried out from November 2023 to January 2024 with google scholar sources. Results: Factors that influence students' desire to volunteer are the length of education, training that has been obtained, transmission of the COVID-19 virus, availability of personal protective equipment, student housing. Conclusion: Educational institutions and volunteer institutions can work together to form guidelines in increasing the interest and skills of nursing students to volunteer during disasters by paying attention to these factors starting from the disaster learning curriculum.